Infectious risk in ostomy patient: the role of nursing competence : NURSING COMPETENCE IN INFECTIOUS RISK - Foà, Chiara; Bisi, Elena; Calcagni, Alessandra; Goldoni, Alexandra; Moscatelli , Maria Paola; Pellicani, Vincenza; Uccelli, Stefano; Sarli , Leopoldo; Artioli, Giovanna (Acta Biomedica Atenei Parmensis, 2019)
Background and aim of the work: The risk of peristomal infections in ostomy patients is well documented in the literature. The nurse and the stoma therapist play a fundamental role in the management and prevention of ostomy-related infections. The present research aims to investigate, across the different phases of the nursing process, the level and characteristics of nursing expertise and highlight their impact on reducing infectious risk in ostomy patients. Methods: 40 nurses (31 women; mean age = 47.7; SD= 7.68) working with ostomy patients were interviewed, in three Italian Local Healthcare Company (LHC) of Northern Italy, Central Italy, and Southern Italy. Nurses compiled a semi-structured ad-hoc interview concerning the level of skills, training, and experience with ostomy patients. The declared expertise has been compared to the retrospective archive data related to the peristomal skin infections of the three LHC. Results: Several differences have emerged in terms of nurses’ expertise and care settings: for instance, ostomy complications in Southern Italy being managed with specific checklists, whereas in the Northern Italy complications being managed by stoma therapists and in Central Italy by hospital ward general nurses. Moreover, the level of professional training was very important for all respondents. The incidence rates of infections after training are lower than a pre-training period. Conclusions: The expertise resulting from specific training for nurses and stoma therapists are crucial for the management of the ostomy and the prevention of complications, in particular of infections. If the training reduces the peristomal complications, therefore, it is necessary to provide and preserve nurses’ expertise, to guarantee patients an optimal treatment path.